A Phase 1, Randomized, Open‐Label, Safety, Tolerability, and Comparative Bioavailability Study of Intranasal Dihydroergotamine Powder (STS101), Intramuscular Dihydroergotamine Mesylate, and Intranasal DHE Mesylate Spray in Healthy Adult Subjects - Albrecht, Detlef; Iwashima, Mic; Dillon, Debbie; Harris, Stuart; Levy, Jeff (Headache, 2020)
Objective To investigate and compare the safety and the pharmacokinetics of dihydroergotamine (DHE) after administration of intranasal DHE powder (STS101), intranasal DHE spray (Migranal®), and intramuscular (IM) DHE injection in healthy subjects. Methods This was a 2‐part, active‐controlled, 3‐period crossover study over 3 weeks, separated by 1‐week washout periods. In part 1, 3 ascending dosage strengths of STS101 (1.3, 2.6, and 5.2 mg) were administered to 15 healthy subjects with no history of migraine. In part 2, 27 healthy subjects were administered 1 dose each of STS101 5.2 mg, Migranal DHE Mesylate Liquid Nasal Spray 2.0 mg, and IM DHE Mesylate 1.0 mg in a randomized order. Liquid chromatography, tandem mass spectrometry was used to determine plasma levels of DHE and its major metabolite, 8′OH‐DHE. Pharmacokinetic parameters (Cmax, Tmax, AUC0‐2 h, AUC0‐48 h, AUC0‐inf, and t1/2) for DHE and metabolite were calculated. Geometric means and 90% confidence intervals of log‐transformed data were calculated and the ratio of means compared. Safety was evaluated by monitoring adverse events, vital signs, electrocardiograms, subjective and objective assessments of nasal signs and symptoms, and changes in laboratory parameters. The study is registered as NCT03874832. Results Forty‐three subjects were enrolled and received study medication. Forty completed all study activities, 14 in part 1 and 26 in part 2. In part 1, DHE plasma levels showed a dose‐dependent increase, with STS101 5.2 mg reaching a mean Cmax of 1870 pg/mL with a Tmax of 23 minutes. In part 2, STS101 5.2 mg showed rapid absorption, achieving mean DHE plasma concentrations of 1230 and 1850 pg/mL at 10 and 15 minutes after administration, respectively. In comparison to Migranal, STS101 5.2 mg showed approximately 2‐fold higher Cmax (2175 vs 961 pg/mL), AUC0‐2 h (2979 vs 1316 h × pg/mL), and AUC0‐inf (12,030 vs 6498 h × pg/mL), respectively. The mean AUC0‐inf of STS101 5.2 mg was comparable to IM DHE (12,030 vs 13,650 h × pg/mL). STS101 5.2 mg showed substantially lower variability compared to Migranal for Cmax (41% vs 76%), AUC0‐2 h (39% vs 75%), and AUC0‐inf (39% vs 55%). The incidence of treatment emergent AEs (TEAEs), all mild and transient, reported in parts 1 and 2 combined was 9/15 (60%), 5/15 (33%), and 16/41 (39%) of the subjects after 1.3, 2.6, and 5.2 mg STS101, respectively, and 4/26 (15%) and 5/27 (19%) of the subjects after IM DHE and Migranal, respectively. Conclusion STS101 showed rapid absorption, achieving effective DHE plasma concentrations within 10 minutes. It achieved substantially higher Cmax, AUC0‐2 h and AUC0‐inf, compared to Migranal suggesting potentially better efficacy than Migranal. Its variability was better than Migranal, thus offering improved consistency of response. AUC0‐inf was comparable to IM DHE, suggesting prolonged action and low recurrence. Additionally, the Cmax was sufficiently low to avoid any significant nausea reported with IV DHE. Thus, STS101 is an easy to administer, non‐injected, acute treatment for migraine, with a favorable tolerability profile and is expected to provide rapid and consistent freedom from pain and associated migraine symptoms without recurrence.